Effect of metal decoration on sulfur-based gas molecules adsorption on phosphorene - Yonghu Wang (Nature Portfolio, 2021)
Abstract Based on first-principles calculation, the adsorption of sulfur-based gas molecules (H2S, SO2, SO3) on various metal-decorated phosphorenes is researched systematically. Eleven metals (Li, Na, K, Rb, Cs, Ca, Sr, Ba, Ni, La, Tl) which can avoid the formation of clusters on the phosphorene are considered. Noticeably, all metal decorations can enhance the adsorption strength of phosphorene to sulfur-based gas molecules except for H2S on Tl-decorated phosphorene. Meanwhile, the adsorption energy (E ads) shows the trend of E ads(H2S) < E ads(SO2) < E ads(SO3) for the same metal decoration case. In addition, some metal-decorated phosphorene systems exhibit intriguing magnetic and electrical variation after sulfur-based gas molecule adsorptions, indicating that these systems are promising to be candidates for the detection and removal of sulfur-based gas molecules.